Penggunaan Zahir Accounting dalam Optimalisasi Pencatatan Keuangan Dyandra Promosindo Surabaya - Margareth Hasian Siagian; Oryza Tannar (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The aim of this research is to analyze the use of financial applications with Zahir accounting software implemented by PT. Dyandra Propertindo Surabaya. The benefit of this research is for all groups/parties, especially those who share the same frequency as the subject and object of research. The research method used is to carry out direct observations or observations at the company, then using the literature study method to increase the literature to match theory with findings in the field from the results of the second method, namely opinion poll interviews, to strengthen the findings from the research. The research results show that the use of financial applications based on Zahir Accounting software at PT. It can be said that Dyandra Propertindo Surabaya has been running for quite a long time and has been implemented properly and correctly in accordance with the flow and process of the application's functions. However, the company said there were still obstacles in implementing this software, mainly the internet network factor. The conclusion of this research is that PT. Dyandra benefits from using Zahir Accounting software from various aspects, including time, accuracy, effectiveness and flexibility in preparing company financial reports.